The Clinicopathological Features and Survival Outcomes of Different Histological Subtypes in Triple-negative Breast Cancer - Liao, Hong-Ye (J Cancer, 2018)
Purpose: To determine the clinicopathological features and survival outcomes of triple-negative breast cancer (TNBC) according to different histological subtypes. Methods: Using the Surveillance, Epidemiology, and End Results database, we included TNBC cases in 2010-2013. The effect of histological subtype on breast cancer-specific survival (BCSS) and overall survival (OS) were analyzed using univariate and multivariate analyses. Results: A total of 19,900 patients were identified. Infiltrating ductal carcinoma not otherwise specified accounted for 91.6% of patients, followed by metaplastic carcinoma (2.7%), medullary carcinoma (1.4%), mixed lobular-ductal carcinoma (1.4%), lobular carcinoma (1.3%), apocrine carcinoma (1.0%), and adenoid cystic carcinoma (0.6%). Medullary carcinoma was more frequently poorly/undifferentiated. Significantly more lobular carcinoma, mixed lobular-ductal carcinoma, and metaplastic carcinoma patients had larger tumors. Adenoid cystic carcinoma, metaplastic carcinoma, medullary carcinoma, and apocrine carcinoma were more frequently node-negative. Lobular carcinoma (16.0%) and mixed lobular-ductal carcinoma (10.4%) more frequently had distant stage at initial diagnosis. Histologic subtype was an independent prognostic factor of BCSS and OS. Compared with infiltrating ductal carcinoma, medullary carcinoma and apocrine carcinoma had better BCSS and OS, while mixed lobular-ductal carcinoma and metaplastic carcinoma had worse survival. Adenoid cystic carcinoma survival was not significantly different from that of infiltrating ductal carcinoma. Conclusions: TNBC histological subtypes have different clinicopathological characteristics and survival outcomes. Medullary carcinoma and apocrine adenocarcinoma have excellent prognosis; mixed lobular-ductal carcinoma and metaplastic carcinoma are the most aggressive subtypes.